Insights into multiscale chemical characterisation for the understanding of berry maturation - Boulet; Emmanuelle Meudec; Marie-Agnes Ducasse; Elissa Abi-Habib; Sophie Le Gall; Xavier Falourd; Benedicte Bakan; Amidou Traore; Geraldine Lucchi; Karine Gourrat; Caroline Peltier; Céline Poncet-Legrand; et al. (OENO One)
Among secondary metabolites, phenolic and volatile compounds are major contributors to wine quality. Their quantities in wines will depend on several factors, their concentrations in grapes but also their extraction rates, along with a number of other factors. Extraction is a complicated process which involves interactions with other compounds; e.g., polysaccharides and proteins. The aim of this work was to evaluate the potential of merging different analytical methods for identifying different compounds at different scales. Known methods in wine analysis, such as phloroglucinolysis, were complemented with methods usually applied to other food products and rarely or never on grapes or wines, such as solid-state NMR and NMR water mobility by 1H MRI. The feasibility of merging these methods was validated on this first trial. While the results did not allow us to answer questions related to the study, they raised other interesting questions to be addressed in future experiments.